A Hospital Based Study of Prevalence of Dry Eye in Tertiary Care Hospital of Nepal - Joshi Shrestha, L.; Kaiti, R. (Kathmandu University Medical Journal, 2021)
Background Dry eye is a common disorder of the tear film that results from decreased tear production, excessive tear evaporation, or abnormality in mucin or lipid components of the tear film associated with symptoms of ocular discomfort. Objective To determine the prevalence of dry eye among patients above 40 years attending out-patient department in a Tertiary Care Hospital of Nepal. Method This was a prospective hospital-based study done at the Department of Ophthalmology in Dhulikhel Hospital, Kathmandu University Hospital for a period of six months from September 2016 to February 2017. All the patients above 40 years of age, attending out patients department were screened by ophthalmologist using the Ocular Surface Disease Index (OSDI). Those patients who were diagnosed of dry eye by OSDI were further evaluated by Schirmer’s test and Tear film breakup time (TBUT). Result Out of 4470 patients attending Ophthalmology outpatient department 1599 patients were of age above 40 years. The overall prevalence of dry eye according to OSDI questionnaire was 25% (400). The mean age of patient with dry eye was 54 yrs. 169 were males (42.2%) and 231 were females (57.7%). Among them Schirmer’s test was positive in 16.7% (67) and TBUT was positive in 85.7% (343) of the patients with dry eye. Conclusion Dry eye is a common condition among patients attending ophthalmology outpatient department in tertiary care center and is leading cause of ocular discomfort. The prevalence of dry eye was higher among indoor workers than in outdoor workers. Further studies are needed to establish association and risk factor of dry eye.